Provincial economic level analysis in Indonesia based on the geothermal energy potential and growth regional domestic products using cluster analysis. Issue 1 (February 2021) - Idroes, G M; Syahnur, S; Majid, S A.; Sasmita, N R; Idroes, R
Abstract: This study aims to determine the provincial economic level in Indonesia based on geothermal energy potential and growing regional domestic product (GRDP). The data used in this research is secondary data. The type of data is a cross-section from 34 Provinces in Indonesia in 2018. Geothermal Energy Potential Data is obtained from the Ministry of Energy and Mineral Resources (ESDM), and GRDP data for each province is obtained from the Indonesian Central Statistics Agency (BPS). This study divided data into 5 clusters using the k-means method. The results showed that there are 2 provinces in cluster 1, 1 province in cluster 2, 8 provinces in cluster 3, 22 provinces in cluster 4, and 1 province in cluster 5.